Sex differences in hypertension. Do we need a sex-specific guideline? - Cífková, Renata; Strilchuk, Larysa (Frontiers in Cardiovascular Medicine, 2022)
Hypertension is the most prevalent cardiovascular disorder and the leading cause of death worldwide in both sexes. The prevalence of hypertension is lower in premenopausal women than in men of the same age, but sharply increases after the menopause, resulting in higher rates in women aged 65 and older. Awareness, treatment, and control of hypertension are better in women. A sex-pooled analysis from 4 community-based cohort studies found increasing cardiovascular risk beginning at lower systolic blood pressure thresholds for women than men. Hormonal changes after the menopause play a substantial role in the pathophysiology of hypertension in postmenopausal women. Female-specific causes of hypertension such as the use of contraceptive agents and assisted reproductive technologies have been identified. Hypertensive disorders in pregnancy are associated with increased risk of maternal, fetal, and neonatal morbidity and mortality, as well as with a greater risk of developing cardiovascular disease later in life. Hypertension-mediated organ damage was found to be more prevalent in women, thus increasing the cardiovascular risk. Sex differences in pharmacokinetics have been observed, but their clinical implications are still a matter of debate. There are currently no sufficient data to support sex-based differences in the efficacy of antihypertensive treatment. Adverse drug reactions are more frequently reported in women. Women are still underrepresented in large clinical trials in hypertension, and not all of them report sex-specific results. Therefore, it is of utmost importance to oblige scientists to include women in clinical trials and to consider sex as a biological variable.